2013
DOI: 10.1007/s12011-012-9594-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Chromium Excretion in Response to an Insulin Challenge Is Not a Biomarker for Chromium Status

Abstract: Over 50 years ago, chromium (Cr) was proposed to be an essential trace element; however, recent studies indicate that this status should be removed as the effects of Cr supplementation appear to be pharmacological rather than nutritional. The pharmacological basis for Cr's effects can explain the inability of investigators to discover a biomarker for Cr status. One potential biomarker has not been examined to date. Cr is known to be mobilized in the body in response to insulin (or insulin release in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…On the contrary, Anderson et al [ 45 ] observed a reduce Fe content in the tissues of rats supplemented with chromium(III) chloride. Similarly, the results obtained by Ani and Moshtaghie [ 46 ] reported that decreased transferrin saturation and tissue stores of Fe as well as reduce haemoglobin and haematocrit indices in animals fed a diet with a high content of Cr(III). This was an antagonistic competition between trivalent chromium and trivalent iron for binding to apotransferrin [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…On the contrary, Anderson et al [ 45 ] observed a reduce Fe content in the tissues of rats supplemented with chromium(III) chloride. Similarly, the results obtained by Ani and Moshtaghie [ 46 ] reported that decreased transferrin saturation and tissue stores of Fe as well as reduce haemoglobin and haematocrit indices in animals fed a diet with a high content of Cr(III). This was an antagonistic competition between trivalent chromium and trivalent iron for binding to apotransferrin [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 64%
“…did not cause significant changes in content of Fe in the liver and kidney. Likewise, Love et al [ 46 ] found that the supplementary Cr(III) (16–2000 μg kg −1 diet) given for 23 weeks had no effect on the blood iron concentration in ZKL rats. No adverse effects of Cr3 on the Fe status when given to normal and with type 2 diabetes rats for 24 weeks at doses of 250–1000 μg of Cr kg −1 b.w.…”
Section: Discussionmentioning
confidence: 99%
“…However, they observed higher liver Fe level and lower kidney Fe concentrations than their controls in Zucker obese (ZKO) rats [ 17 ]. Also, Love et al [ 56 ] observed that the dietary Cr (16–2000 μg· kg −1 diet) given for 23 weeks had no effect on the blood iron level in Zucker lean (ZKL) rats. Similarly, Clodfelder et al [ 4 ] did not observe adverse effects of Cr3 on the Fe status when given to healthy rats or to the animals with type 2 diabetes for 24 weeks as an aqueous solution at doses of 250–1000 μg of Cr· kg −1 b.m.…”
Section: Discussionmentioning
confidence: 99%
“…Both the plasma concentrations and the hair levels of chromium were associated with intake in different Greek regions. Urinary chromium may not be a valid biomarker for chromium intake [ 162 ]. There is a need for better biomarkers of chromium intake [ 163 ].…”
Section: Amino Acids Proteins Minerals and Trace Elementsmentioning
confidence: 99%